2018
DOI: 10.21100/msor.v16i3.798
|View full text |Cite
|
Sign up to set email alerts
|

The Provision of Mathematics and Statistics Support in Scottish Higher Education Institutions (2017) – A Comparative Study by the Scottish Mathematics Support Network

Abstract: The Scottish Mathematics Support Network (SMSN) was formed in July 2008 with the aim of creating a support network for people working in Scottish universities who were involved with, or wished to be involved with, providing mathematical and/or statistical support for their students. The consensus of the SMSN is that increasingly more students need assistance with their basic mathematical and statistical skills than was the case in the past, and that consequently mathematics support is an area on which universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Whilst intuitively we expect the 'true' overall figure to be closer to 75% than 86%, since institutions are more likely to respond to survey requests if they have provision than if they do not, regardless it shows that mathematics support is extensively available within higher education providers across the UK and Ireland. Further, there exists no evidence in any survey (Ahmed et al, 2018;Cronin et al, 2016) that the provision of mathematics support within institutions is declining. As such mathematics support is now a widely available, accessible and extensively used service within institutions to support students with the challenges that they may face with the mathematical components of their higher education studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whilst intuitively we expect the 'true' overall figure to be closer to 75% than 86%, since institutions are more likely to respond to survey requests if they have provision than if they do not, regardless it shows that mathematics support is extensively available within higher education providers across the UK and Ireland. Further, there exists no evidence in any survey (Ahmed et al, 2018;Cronin et al, 2016) that the provision of mathematics support within institutions is declining. As such mathematics support is now a widely available, accessible and extensively used service within institutions to support students with the challenges that they may face with the mathematical components of their higher education studies.…”
Section: Discussionmentioning
confidence: 99%
“…The previous survey of mathematics support considered the whole of the UK (Perkin et al, 2013). Given the existence of recent, and comprehensive, surveys of mathematics support across the island of Ireland (Cronin et al, 2016) and within Scotland (Ahmed et al, 2018), the decision was taken not to duplicate these. As such, the survey we describe here chooses to focus upon mathematics support only within England and Wales.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2008 however the support community was brought together through the formation of the Scottish Mathematics Support Network (SMSN). A recent report (Ahmed et al, 2018) by the SMSN found that 78% of the Scottish institutions that responded provide mathematics and/or statistics support.…”
Section: Introductionmentioning
confidence: 99%